Diffusion-Reaction Models of Genipin Incorporation into Fibrin Networks - Ninh, Chi (J Mater Chem B, 2015)
Genipin is a naturally derived small molecule that crosslinks compounds containing primary amines including many natural biopolymers. A diffusion-reaction model to predict the rates of delivery and incorporation of genipin into fibrin networks is presented. Genipin crosslink formation within fibrin hydrogels is a multi-step process that requires genipin diffusion and reaction with primary amines in hydrated networks. The reaction rate of genipin into fibrin gels was measured via spectroscopy while the rate of marginal crosslink formation was measured by rheology. Covalent coupling between genipin and primary amines in fibrin gels obeys second-order kinetics in genipin concentration with an effective activation energy of −71.9 ± 3.2 kJ-mol(−1). Genipin diffusion-reaction within fibrin gels exhibits Thiele moduli between 0.02–0.28, which suggests that the systems studied herein are reaction-limited. Genipin-crosslinked fibrin clots are resistant to fibrinolytic degradation as measured by rheology. Finally, active genipin can be delivered from poly(D,L-lactide-co-glycolide) matrices to gels at rates that are comparable to the characteristic rate of incorporation in fibrin networks. Taken together, this work establishes a quantitative framework to engineer controlled release systems for genipin delivery into protein-based hydrogel networks.